Bott functions and the euler characteristic - Bondar', O. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
In terms of the Euler characteristic, we obtain the condition of existence of Bott functions on differentiable manifolds that have a set of critical points formed by connected homeomorphic submanifolds.